Cadmium level trend in liver and kidney of pigs from Serbia during 2014-2018. (September 2019) - Nikolic, D; Jankovic, S; Djinovic-Stojanovic, J; Radicevic, T; Stefanovic, S; Spiric, D; Simunovic, S
Abstract: Concentrations of cadmium (Cd) were measured in samples of liver (n=88) and kidney (n=226) of pigs within the Serbian National Residue Monitoring Program during 2014-2018. Levels of Cd were determined by inductively-coupled plasma mass spectrometry. All of the pigs had measurable amounts of Cd in liver and kidney, but none of the analyzed samples exceeded MRL for Cd – 0.5 and 1.0 mg/kg, respectively. The maximum Cd concentration in kidney amounting to 0.864 mg/kg was established in the first year of the residue monitoring program (2014). No statistically significant differences in Cd levels in liver samples during the examined period were observed, while statistical differences were established only between Cd levels in kidney collected in 2014 and 2015. On the basis of statistical analysis, it can be concluded that Cd levels have not increased in the analyzed organs during the investigated period.